2019
DOI: 10.1002/aoc.5204
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically separable mesoporous silica‐supported palladium nanoparticle‐catalyzed selective hydrogenation of naphthalene to tetralin

Abstract: A novel magnetically separable mesoporous silica-supported palladium catalyst was designed and prepared for the selective hydrogenation of naphthalene to tetralin, which is an important transformation from a practical viewpoint. In the catalyst, Pd nano grains were dispersed uniformly and protected within the mesoporous silica shells being coated on the Fe 3 O 4 core, so that the durability of the catalyst could be significantly improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Because the amount of Pd was small, and the Pd nanoparticles were well dispersed on the support. [4] The XRD patterns of Pd/Al 2 O 3 , Pd/ZSM-5, Pd/SBA-15, and the pristine supports are shown in Figure S5. Similarly, no significant peak of Pd or PdO was detected in all the as-prepared catalysts.…”
Section: Chemistryselectmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the amount of Pd was small, and the Pd nanoparticles were well dispersed on the support. [4] The XRD patterns of Pd/Al 2 O 3 , Pd/ZSM-5, Pd/SBA-15, and the pristine supports are shown in Figure S5. Similarly, no significant peak of Pd or PdO was detected in all the as-prepared catalysts.…”
Section: Chemistryselectmentioning
confidence: 99%
“…For instance, naphthalene can be transformed into the much-needed bicyclic alkane through hydrogenation saturation, which increases the heat value when used as fuel and improves the stability when used as solvent. [1][2][3][4][5] Complete saturation hydrogenation of naphthalene is a hard task due to the difficulty of breaking the stable double bonds. Because all the electrons disperse and flow on the ten carbons to generate a stable big π bond in naphthalene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that transition metal oxide nanostructures are broadly employed because of having surface area with high specific, chemical permanence, and electrochemical property at nanoscale form along with employment in technology and applied science. [23][24][25][26][27] MWCNTs due to having an area with large surface and capacity with high adsorption have been widely studied. [28] TiO 2 has attracted increasing attention due to excellent chemical stability, nontoxicity, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Later, magnet particles supported heterogeneous catalysts, which significantly simplified the recycling process and improved recovery began to prevail. [13][14][15] Among these attempts, the Fe 3 O 4 nanoparticles based supports are most often chosen due to easy preparation and modification. For instance, Huo et al reported a magnetically separable heterogeneous platinum catalyst bearing ligands of imidazolyl Schiff base.…”
Section: Introductionmentioning
confidence: 99%